How to use your reading in your essays - Godfrey, Jeanne (New York Palgrave Macmillan, 2009)
Featuring real texts and examples of student writing, this practical book guides the undergraduate student through the process of effectively using reading in their essays. It covers - selecting what to read, how to quote, paraphrase and summarise sources, through to spotting and correcting mistakes in the final essay.